COLLABORATION BETWEEN LIUNGGUNUNG KINDERGARTEN AND LINGGARSARI VILLAGE GOVERNMENT IN MGING TDBA POLICY THROUGH THE BIPTAKA PROGRAM AS AN INNOVATION IN FAMILY EDUCATION AND VILLAGE INDEPENDENCEANA - Zhafira Fartimatuzahra Hidayat; Nurul Fauziah; Yuwan Fijar Anugrah; Muhammad Fahmi Rizal; M.S Ridwanulloh; Khaidir Maulana; Solihah Bagus (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to examine the management of the Tatanén di Balé Atikan (TDBA) policy at TK Pembina Liunggunung through a collaborative program with the village government called BIPTAKA (Budidaya Ikan Patin Kelas Orang Tua dan TDBA). The program represents an environmental-based learning innovation that integrates educational agriculture, family engagement, and local village potential. The study employed a descriptive qualitative approach, collecting data through observation, in-depth interviews with teachers, the principal, parents, and village officials, as well as documentation. Data were analyzed thematically to explore the forms of collaboration, learning benefits, and the impact of the TDBA policy on children’s learning environments. The findings reveal that the BIPTAKA program successfully strengthened the management of TDBA as a contextual learning space rooted in local culture. Children demonstrated greater enthusiasm and active participation in experiential learning, while parents became more involved in the educational process. The program also reinforced values of cooperation, responsibility, and environmental awareness. In conclusion, the implementation of the TDBA policy through the BIPTAKA collaboration serves as a good practice in developing education based on village potential and local culture.